Ancient Israel: what do we know and how do we know it? - Grabbe, Lester L. (Criminal Practice Ser., 2017)
Cover -- Half-Title -- Title -- Copyright Page -- Dedication -- Contents -- Abbreviations -- Preface to the Second Edition -- Preface to the First Edition -- Part I: Introduction -- Chapter 1: The Principles and Methods of Investigating the History of Ancient Israel -- 1.1 Aims -- 1.2 Concepts and Complications: The Question of Sources and Methods -- 1.2.1 The Place of the Social Sciences -- 1.2.2 The Longue Durée -- 1.2.3 The Model and Method of Classical Studies -- 1.2.4 Using Archaeology as a Source -- 1.2.4.1 General Comments -- 1.2.4.2 Terminology of Archaeological Periods -- 1.2.4.3 Use of Survey Data -- 1.2.4.4 The Debate Over the 'Low Chronology' -- 1.2.4.5 Estimating Population -- 1.2.4.6 The Stratigraphy of Samaria -- 1.2.4.7 Reinterpretation of the Jochan Seal -- 1.2.4.8 Problems with Forgeries -- 1.2.5 Ethnicity -- 1.2.6 Ideology and Neo-Fundamentalism -- 1.2.7 'Maximalists', 'Minimalists' and the ad hominem Argument -- 1.3 The Contemporary Practice of Writing Israel's History -- 1.3.1 Developments in General Historiography -- 1.3.2 Forty Years of Debate Among Biblical Scholars -- 1.3.3 Principles of Historical Method Used in this Book -- Part II: Historical Investigations -- Chapter 2: Second Millennium: Middle and Late Bronze Ages (2000-1300 BCE) -- 2.1 Sources -- 2.1.1 Archaeology -- 2.1.2 Egyptian Texts -- 2.1.2.1 Execration Texts -- 2.1.2.2 Amarna Letters -- 2.1.2.3 The Story of Sinuhe -- 2.1.3 Ugaritic Texts -- 2.1.4 Mesopotamian Texts -- 2.1.5 Biblical Text -- 2.2 Analysis -- 2.2.1 Peoples/Ethnic and Social Groups -- 2.2.1.1 Hyksos -- 2.2.1.2 Amorites (Amurru) -- 2.2.1.3 'Apiru/Ḫaberu -- 2.2.1.4 Shasu (Shosu, Š3św, Sutu) -- 2.2.1.5 Canaanites -- 2.2.2 Question of the Patriarchs -- 2.3 Synthesis -- 2.3.1 First Part of Second Millennium (ca. 2000-1600/1500 BCE) -- 2.3.1.1 Egypt.